Multiscale Textured Mesh Substrates that Glide Alcohol Droplets and Impede Ice Nucleation. Issue 8 (28th March 2022) - Bajpayee, Aayushi; Rivera-Gonzalez, Natalia; Braham, Erick J.; Alivio, Theodore E. G.; Anita,; Alvi, Scheherzad; Li, Chenxuan; Cool, Nicholas; Al-Hashimi, Mohammed; Fang, Lei; Banerjee, Sarbajit
Abstract : Textured surfaces are commonly designed to preclude wetting by water. The design of surfaces that are not wetted by alcohols represents a considerable challenge given the low surface tension, viscosity, and density of these liquids. Herein, a hierarchically textured plastronic architecture that can suspend alcohol droplets in a metastable Cassie–Baxter regime is presented. As a result of microtexturation of the underlying stainless steel mesh, multiscale texturation derived from ZnO tetrapods, and surface functionalization with perfluorinated‐polyhedral oligomeric silsesquioxanes, the surfaces glide aliphatic alcohols, water, and n ‐hexadecane. The design of surfaces not wetted by alcohols is particularly relevant to "point‐of‐care" environments. Because of the minimized interfacial contact areas, the textured surfaces further greatly inhibit ice nucleation at solid/liquid interfaces. High‐speed video imaging of the freezing and droplet impact shows that the textured surfaces delay ice nucleation by inhibiting heterogeneous nucleation, more effectively channel kinetic energy upon droplet impact to break up impinging droplets, and greatly limit frost formation. Once ice forms, its adhesion is substantially diminished by about three orders of magnitude as compared with planar substrates. The results demonstrate a scalable spray deposition method to generate surfaces for enabling the deterministic flow of liquids as well as inhibit ice formation. Abstract : Textured surfaces are commonly designed to preclude wetting by water. The design of surfaces that are not wetted by alcohols represents a considerable challenge given the low surface tension, viscosity, and density of these liquids. Herein, a hierarchically textured plastronic architecture for enabling the deterministic flow of liquids as well as to inhibit frost and ice formation is presented.